Hydro-Geophysical Assessment of Freshwater-Lens Thinning and Saline Upconing in Three Inhabited Atolls of the Northern Cook Islands - Mary-Jane Wood; Eva Browne; Tiare Wichmann (Sriwijaya Journal of Environment, 2026)
Background: Freshwater lenses are the principal source of potable water for the low-lying coral atolls of the Northern Cook Islands, yet they are acutely vulnerable to sea-level rise, tidal forcing and over-abstraction. Objective: This study quantified freshwater-lens thinning and saline upconing across three inhabited atolls (Rakahanga, Manihiki and Pukapuka) and identified the environmental and anthropogenic drivers of degradation. Methods: Electrical resistivity tomography delineated the freshwater–seawater interface, while 24 community wells were sampled in the 2024 wet and dry seasons for electrical conductivity (EC), chloride, tidal amplitude, abstraction and recharge. Data were analysed offline with ANOVA (Tukey HSD, η²), Pearson correlation, multiple regression, principal component analysis (PCA) and salinisation indices, benchmarked against WHO/US-EPA guidelines. Results: Mean lens thickness was critically low at 4.34 ± 1.01 m and differed significantly among atolls (F(2,21) = 45.73, p < 0.001, η² = 0.813), thinning from Rakahanga (5.45 m) to Pukapuka (3.27 m). Chloride (mean 405 mg/L) exceeded the 250 mg/L WHO guideline in 19 of 24 wells and was inversely correlated with thickness (r = −0.835, p < 0.001). Regression explained 83.5% of the variance (adjusted R² = 0.810; F(3,20) = 33.69, p < 0.001), and PCA resolved a single salinisation axis explaining 77.5% of variance; the Groundwater Quality Index rose from 106 to 179 along the same gradient. Conclusion: The freshwater lenses of the Northern Cook Islands are thin, saline and actively degrading under combined tidal forcing and manageable anthropogenic abstraction, requiring optimised pumping, rainwater augmentation and continuous monitoring to safeguard atoll water security.